Effects of nitrogen on the mechanical properties of cold rolled TRIP-aided steel sheets - Baik, Seung Chul; Park, Sung-Ho; Kwon, Hicion; Kim, Dong-Ik; Oh, Kyu Hwan (IRON STEEL INST JAPAN KEIDANREN KAIKAN, 2006)
Tensile tests were conducted in order to study the effects of nitrogen on the mechanical properties of the 0.2C-1.5Mn-1.5Si-0.04Al-(0.003-0.015)N steels often annealing at 800-830 degrees C, followed by the austempering at 400-450 degrees C. The results show that both tensile strength and elongation increase and the balance of tensile strength X elongation are improved upon nitrogen addition to the TRIP steel. It was found that the density of AlN precipitates increases with addition of nitrogen. The volume fraction of retained austenite increases due to AlN precipitation, because the precipitates retard the transformation of austenite during cooling and austempering. As a larger volume fraction of austenite remained after annealing has been transformed to martensite during deformation, elongation as well as strength has increased in the nitrogen added steel. It is also observed that the average grain size of ferrite and bainite decreases because of AlN precipitation that hinders grain growth. The refinement of ferrite and bainite by AlN precipitates also contributes to the increase in the strength of nitrogen added steels.
Keywords: DUAL-PHASE STEELS; RETAINED AUSTENITE CHARACTERISTICS; TRANSFORMATION-INDUCED PLASTICITY; ASSISTED STEELS; SI; BAINITE; BEHAVIOR; SILICON; DEFORMATION; STABILITY